Evaluasi Program Parenting Pada Pendidikan Anak Usia Dini (PAUD) Di Kota Mataram - Maimun - (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2016)
The objective of this research was to understand comprehensively about the enforceability of parenting program on early childhood education (PAUD) in Mataram pre-schools. The study applies qualitative approach the focuses on evaluation in pre- shool education in Mataram. The data were collected through interviews, observation, documentation, and questionnaire. This Study shows that (1) the background of the parenting program implementation was lack of parents' supports of child education; (2) the implementation of parenting program in pre-shools has fulfilled the requirements laid down in the guideline book; (3) most of pre-school institutions have implemented parenting program in accordance with the technical guideline book; and (4) the majority of parents' understandings of child nutrition, treatment, upbringing, and protection have signivicantly increased upon the implementation of the program.